(3YbO GdMSGH GdLGQj GdVhGHW GdbGfhfjI hGdTHgGJ GdTQYjI aj Gdabg GdGSdGej hGdbGfhf GdhVYjs - (3GdeUQj(B, (3YHGS eUWais ((3GdGScfOQjIs (3OGQ GdLGeYI GdLOjOIs, 2004)
(3eGgjI YedjI GdMSGH GdLGQj , GdVhGHW GdbGfhfjI GdMGceI dMQcI GdMSGH GdLGQj , GdGKGQ GdbGfhfjI GdfGTFI , VhGHW GfJgGA YedjI GdMSGH GdLGQj , eOi GJSGb CMcGe GdMSGH GdLGQj eY GdTQjYI GdGSdGejIs
Keywords: (3GdHfhc(B-(3GdMSGHGJ GdeUQajIs; (3GdHfhc(B-(3abg GSdGejs